Assessment of a Test for the Screening and Diagnosis of Celiac Disease. Issue 1 (10th November 2014) - Porcelli, Brunetta; Ferretti, Fabio; Vindigni, Carla; Terzuoli, Lucia
Abstract : Background: Celiac disease (CD) is an immune‐mediated intolerance to dietary gluten, affecting genetically predisposed individuals. ELISA‐based serological tests help to decide if further duodenal biopsy is necessary, for this the diagnostic kits have to be accurate, specific, and sensible. In this study, we investigate the performance of an ELISA that uses the purified cross‐linked complex of tissue transglutaminase and gliadin, referred as the "neoepitope" ( AESKULISA ® tTG New Generation), as antigen. Methods: We evaluated 41 newly diagnosed celiac patients, 18 celiac patients on gluten‐free diet, and 169 controls, comprising healthy subjects, patients affected by other autoimmune diseases, and patients affected by several non‐autoimmune diseases. Results and Conclusion: The assay has an excellent performance. Due to its high level of diagnostic accuracy, this assay constitutes a new approach for the screening of celiac patients not only for the diagnosis of CD, but also for monitoring patients on gluten‐free diet and their compliance. Moreover, cases of neoepitope‐positive subjects who were tested negative with "classical" serological markers could have a predictive value for this pathology. This aspect will require further studies of elaboration.